Two approaches to evaluate perception about food - Conti, Ana Carolina [UNESP]; Moreira, Ana Laura Fermoselli [UNESP]; Lamana, Breno Silva [UNESP]; Marani, Luana Rachel Salgueiro [UNESP]; Dias-Faceto, Liara Silva [UNESP] (FapUNIFESP (SciELO), 2024)
Objective The aims of this research were to investigate the perception about foods in Brazil through two studies: 1) to investigate the perception about the NOVA classification of foods; and 2) to investigate the perception regarding the caloric value of fast foods and restaurant meals. Methods The two studies were carried out online using Google Forms. In study 1 (n=156), participants received twenty-five food concepts and were asked to associate each one with one of the five categories: unprocessed, minimally processed, culinary ingredients, processed and ultra-processed. In study 2 (n=184), images of eight meals (four of fast foods and four of restaurant meals) were provided and participants were asked to group them, as they deemed necessary, depending on the caloric value that each meal provided. After that, the individuals were asked to rank the previously formed groups from the most caloric to the least caloric. Results Participants perceived which foods are unprocessed and ultra-processed, as proposed by NOVA classification, although there was some confusion and misunderstanding about some foods, such as powdered milk, and the culinary ingredients group. Moreover, participants did not perceive the real caloric values of fast-food meals nor restaurant meals. Meals were ranked differently from their real caloric value and participants thought, in general, that fast foods are more caloric than restaurant meals. Conclusion The studies showed that Brazilians have difficulties in perceiving information about foods, i.e., to reach the population regarding food is neither simple nor trivial, highlighting the need to educate the population about it.
Diferentes abordagens para avaliação da percepção sobre alimentos
Keywords: Alimentos ultraprocessados; Classificação NOVA; Fast Food; Fast foods; NOVA classification; Ranking test; Sorting task; Teste de classificação; Teste de ordenação; Ultra-processed food